A cost‐effective LoRa‐based customized device for agriculture field monitoring and precision farming on IoT platform. (3rd November 2020) - Swain, Mahendra; Hashmi, Mohammad Farukh; Singh, Rajesh; Hashmi, Abdul Wahab
Summary: Low‐power wide area networks (LPWAN) applications are emerging as a new paradigm, over Internet of Things (IoT) platform. LoRa (long range) is playing a key role in information exchange between motes. This paper illustrates a mathematical optimization technique of LoRa modulation, i.e., frequency shift chirp modulation. Mathematical optimization for low power and LoRa has been validated with customized hardware designed for agricultural application. The performance analysis with channel modulation is mentioned in the networks. LoRa link budget concerning various obstacles calculated and losses are noted during testing. In context to the agricultural application, customized motes have been deployed in an agricultural field for field monitoring. The mathematical model is validated using a hardware device. Further data collection and data analysis are mentioned. Code optimization techniques are implemented to improve the overall efficiency of the device. Localization of sensor nodes also discussed to cover all the area of coverage. A comparative analysis is a showcased between SNR (signal‐to‐noise ratio) and RSSI (received signal strength indicator). Abstract : In this study, a novel LoRa‐based framework for agriculture field monitoring applications over IoT platform is purposed. A customized hardware device using LoRa architecture has been fabricated and deployed in the field. The device is enabled using RF frequency and Wi‐Fi both for smooth operations depending on the availability of the network. Further, an optimized embedded firmware used in the device to improve the performances. Critical parameters like SNR (Signal to Noise Ratio), RSSI (Received Signal Strength Indicators), and LoRa link budget were calculated on custom‐built LoRa testbed. The performance optimization is showcased for the purposed device in comparison to the existing models.